Does fatigue influence joint-specific work and ground force production during the first steps of maximal acceleration? - Vial, S.; Wilkie, J. C.; Turner, M.; Scanlan, M.; Blazevich, A. J. (Scandinavian Journal of Medicine & Science in Sports, 2023)
During initial acceleration, the first steps of a maximal-effort (sprint) run often determine success or failure in the capture and evasion of an opponent, and is therefore a vital factor of success in many modern sports. However, accelerative events are commonly performed after having already run considerable distances, and the associated fatigue should impair muscle force production and thus reduce acceleration. Despite this, the effects of running-induced fatigue on our ability to accelerate as well as the running technique used to achieve it have received little attention. We recorded 3-D kinematics and ground reaction forces during the first three steps of the acceleration phase from a standing start before and after performing a high-speed, multi-directional, fatiguing run-walk protocol in well-trained running athletes who were habituated to accelerative sprinting. We found that the athletes were able to maintain their acceleration despite changing running technique, which was associated with use of a more upright posture, longer ground contact time, increased vertical ground reaction impulse, decreased hip flexion and extension velocities, and a shift in peak joint moments, power, and positive work from the hip to the knee joint; no changes were detected in ankle joint function. Thus, a compensatory increase in knee joint function alleviated the reduction in hip flexor-extensor capacity. These acute adaptations may indicate that the hip extensors (gluteal and hamstring muscle groups) were more susceptible to fatigue than the ankle and knee musculature, and may thus be a primary target for interventions promoting fatigue resistance.